Variation in mandible shape and size due to osteoporosis: Geometric morphometrics study - Warli Ferreira (International Journal of Interdisciplinary Dentistry, 2023)
Objective: Assessing whether it is possible screening women with osteoporosis through geometric morphometrics based on panoramic x-ray. Materials and Methods: Leukoderma women, after menopause, 40 years old (or older), with confirmed medical diagnosis of presence, or absence, of osteoporosis through bone densitometry examination. (N = 62). Measurements taken through panoramic X-ray based on geometric morphometrics. All x-rays were taken twice by the same researcher. Procrustes superimposition was assessed through Cartesian coordinates generated from anatomic landmark and semilandmarks. Regression Analysis, Multivariate Analysis of Variance (MANOVA), discriminant function and cross validation analysis, and Thin plate spliness in MorphoJ software were carried out. Subsequently, Fluctuating Asymmetry Analysis (FA) was conducted and ANOVA was performed to assess differences in centroid size. Results: Significant values were recorded for mandible shape (p<0.01) through MANOVA. Significant values (P<0.01) were also found through discriminant function analysis between groups of women with, and without, osteoporosis. Fluctuating asymmetry analysis showed significant differences in mandible shape and size between sides (p<0.01). Conclusions: Geometric morphometrics proved to be effective in screening and identifying elderly leukoderma women with, or without, osteoporosis based on panoramic x-rays. This is a promising technique to diagnose or identify patients with some health condition.